(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Currently, conducting business over the electronic network or Internet is very advantageous and has become a global business phenomenon. The increasing number of firms using Internet business methods has raised intense competition among firms. The main challenge faced by firms is that it is easy for other parties to imitate an Internet business method. In order to protect an Internet business method from imitation, business firms realized that there is a need to protect business methods using Patent Law. However, attempts to patent Internet business method have raised controversial patentability issues and dealing with copyright law. Therefore, this paper attempts to examine the issue of Internet business method and its patentability from the perspective of Patent Law in Malaysia. This paper concluded that Internet business method patentability is very dependent on the interpretation of the Patent Law of different national governments.